Compensation structures and firm value / Dong Heon Byun, Jinbae Kim, and Joon Yong Shin - Byun, Dong Heon; Kim, Jinbae (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2007)
This paper studies the effects of the performance-based compensation system and the Age-Wage structure which pays lower (higher) compensation than the industry average during employees’ early (later) service periods. Previous studies show that both compensation systems have positive effects on firm value. The paper extends the results and shows the effects of the compensation systems on major factors of firm value. Empirical results using employee-wage data of Korean firms show that the Age-Wage structure contributes to firm value through the enhancement of ROA, cost reduction and an improvement in labor productivity, and the performance-based compensation system does so through sales growth